Brics’ current economic position and perspectives of its progress - Pykhtina, M.S. (ХНУ ім. В. Н. Каразіна, 2012)
This paper accounts for the problem of economic integration and its global influence on world policy and trade. The research was built on the analysis of BRICS. Its members, association of Brazil, Russia, India, China and South Africa, are five cultures with markedly different worldviews in terms of politics, philosophy and economics. The members of the group consider themselves to be partners in an effort to gain global economic supremacy in the coming decade. BRICS has a potential to play a crucial role in the growing influence of developing countries on global political, economic and financial systems. At the same time, BRICS united the countries that are the most vigorously developing on the background of the economic decline in North America and Europe.
В данной статье представлены результаты изучения вопроса экономической интеграции, а также ее влияния в глобальном масштабе на мировую политику и торговые отношения. Исследование было проведено на основе анализа объединения БРИКС. Его члены, Бразилия, Россия, Индия, Китай и ЮАР – это пять культур с заметно отличающихся мировосприятием касательно вопросов политики, философии и экономики. Члены этой группы видят себя в качестве партнеров в достижении цели обладания глобальным экономическим первенством в ближайшем десятилетии. БРИКС имеет потенциал, чтобы сыграть решающую роль в увеличивающемся влиянии развивающихся стран в глобальной политической, экономической и финансовой системах. В то же время, БРИКС объединяет страны мира, которые наиболее динамично развиваются на фоне экономического упадка в Северной Америке и Европе.
Keywords: BRICS; developing countries; global economic supremacy; economic integration